Answer:
Use the formula for the distance between two points: d = √((x2 – x1)2 + (y2 – y12))
Step-by-step explanation:
d = √((5 – 0)2 + (2 – 0)2
d = √(25 + 4) = √(29) ≈ 5.385
Answer:
[tex]\sqrt{29}[/tex]
Step-by-step explanation:
Use the distance formula. [tex]\sqrt{(x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2}}[/tex]
Plug in the coordinates into the equation. [tex]\sqrt{(2-0)^{2}+(5-0)^{2}}[/tex]
Solve the distance formula. [tex]\sqrt{(2)^{2}+(5)^{2}}[/tex] --> [tex]\sqrt{4+25}[/tex] --> [tex]\sqrt{29}[/tex]